Evaluating Performance in Vocational Education: Determinant Factors of Successful University-Industry (UI) Partnerships - Wahyudi, Kurniawan Sigit; Sofyan, Herminarto; Wagiran , Wagiran; Bin Abd Samad , Noorazman (Journal of Technical Education and Training, 2025)
Efforts to overcome the gap between graduate absorption capacity and market demand require collaboration between University-Industry (UI). So, collaboration between UI is important to improve the quality of graduates. This study aims to explore the success factors of UI partnerships, especially vocational education in improving the quality of graduates and field users. The research approach used is quantitative with a survey design. The research sample consisted of 450 participants including 173 lecturers and 277 industry practitioners with purposive sampling techniques. The PLS-SEM technique was used to test the structural model involving 10 variables, 50 constructs, and 25 hypotheses. The results showed that the success factors of UI partnerships can be explained by 72.90% to 93.20% of the partnership success indicators. Adaptability factors (93.20%), performance assessment (92.70%), facilities (92.20%), and continuous improvement (91.70%) are the main success factors, while the acculturation factor of industrial values has the lowest contribution (72.90%). The structural model can explain the impact of partnerships by 65.90% and 62.30% on the dimensions of UI partnership success. This study contributes to the adjustment, implementation, and standardization of industry-based curriculum needs, to increase the absorption of graduates in the industrial world. The novelty of this study lies in identifying specific factors that contribute significantly to the success of UI partnerships in the context of vocational education.